Food price inflation in India: The growing economy with sluggish agriculture - Sasmal, Joydeb (2015)
India is experiencing high rate of economic growth in the last two decades but the growth has been coupled with high rate of food price inflation. The growth has been very uneven across sectors with agriculture remaining very sluggish. The increase in per capita income has significantly increased the demand for food but agricultural production has failed to keep pace with the growing demand. The theoretical explanations and time series econometric results establish that increase in per capita income and shortage in supply are responsible for price rise. There is no long run relationship between money supply and agricultural price. Increasing public expenditure and unfavorable foreign exchange rate have some effects on price although the results are not robust.